The Influence of Income, Knowledge, and Time Period on Customer Decisions to Take Financing at PT. BPRS ADECO Langsa - Syahvindra, Meutia; Puspita Sari, Juli Dwina (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2024)
When taking out murabahah financing at a BPRS, customers will always consider their income. Customer income is very important because it can determine the customer's ability to make installment payments. Apart from income, when taking out financing at a bank, customers can be influenced by other factors such as the customer's knowledge of a product. Apart from that, another factor that can influence a customer's decision to take out financing is the time period. This is because the financing payment period varies depending on the length of time agreed between the customer and the bank. Therefore, researchers are interested in conducting research on income, knowledge and time period on customers' decisions to take financing. The research method is quantitative with an associative approach. The sample using the limeshow formula of 100 people. The results of the research showed that: (1) Variables interested in conducting research on income, knowledge and time period on customer's decision to take financing. (2) The knowledge variable on customer decisions in taking financing at PT BPRS Adeco Langsa is 0.000 < 0.05 and tcount 5.697 > ttable 1.984. (3) The time period variable for the customer's decision to take financing at PT BPRS Adeco Langsa is 0.341 > 0.05 and tcount 0.957 < ttable 1.984. (4) The income, knowledge and term variables can be said to have a simultaneous influence on customer decision variables in taking financing at PT BPRS Adeco Langsa. With test results Fcount 34.058 > Ftable 2.696 and Sig. 0.000 < 0.05. The R2 value is 51.6% and the remaining 48.4% is influenced by other variables outside this research.